Hardware design of real-valued NSCT transform for biomedical video compression. (2021) - Krishnamoorthy, Raja; Venugopal, D.; Sujatha, M.; Sengan, Sudhakar; Bharatiraja, C.; Jayasankar, T.
Abstract: Number based Non-Subsampled Contourlet Transform (NSCT) diminishes the difficulty of the transformation operation kernel in biomedical video compression by dispensing the requirement for floating number mathematics. Yet, the dynamic scope of INSCT is huge and in this manner, equipment cost is more. In this manuscript, an innovative transformation operation kernel for biomedical video compression is projected which utilizes a novel set of complex and real- esteemed -NSCT coefficients. The projected NSCT decreases the equipment cost, area utilized and propagation time by diminishing the complication with intermediary information duration. Proposed transformation can be implemented by digit parallel multiplications and serial shift operations. Thus the itinerant fault can be decreased by standardize this numeral information and shift quantity for Biomedical video compression. Intermediary information duration and area, power consumption of the proposed method is fewer.